Implementation Millennium Development Goals in Nursery - Wejdan Abdullah Alboti; Amal Hussain Aljubran; Badryah Mohammed Alsaiyegh; Zainab Hussain Alqanbar; Ali Ya'aqoub Al Jubaily; Rbab Hussin Buhelal; Ahlam Abdulwahab Albeladi; Zahra Hussein Al Salamah; Sukinah Hussain Alobaid; Fatimah Abdullah Alnuwaysir; Ismail Yousef Alabdullah; Maryam Khalil Alhabib; et al. (International Journal of Scientific Research and Innovative Studies, 2022)
The Millennium Development Goals (MDGs) provided a framework for global action to address key social, economic, and health issues, including those related to maternal and child health. In the context of nursery care, the implementation of MDGs has played a significant role in improving the quality of care provided to infants and young children. This mini-review explores the implementation of MDGs in nursery care settings, focusing on their impact on maternal and child health outcomes.